Adapting an organ‐on‐chip device to study the effect of fetal sex and maternal race/ethnicity on preterm birth related intraamniotic inflammation leading to fetal neuroinflammation. (2nd November 2022) - Richardson, Lauren S.; Emezienna, Nkechinyere; Burd, Irina; Taylor, Brandie D.; Peltier, Morgan R.; Han, Arum; Menon, Ramkumar
Abstract: Problem: Fetal neuroinflammation has been linked to preterm birth‐related intraamniotic infection and inflammation; However, the contribution of fetal sex and maternal race/ethnicity is unknown. To determine if fetal sex and maternal race/ethnicity influence neuroinflammation, an organ‐on‐chip (OOC) model were established under normal or pathologic conditions utilizing amniotic fluid. Method of study: OOC is composed of two‐cell culture chambers connected by Type IV collagen‐coated microchannels. Human fetal astroglia (SVGp12) and microglia (HMC3) were co‐cultured at an 80:20 ratio in the inner chamber. The outer chamber contained amniotic fluid (AF) from male and female fetuses of White Hispanic (WH) and African‐American (AA) pregnant women with or without lipopolysaccharide (LPS‐100 ng/ml) and incubated for 48 h. Glial migration (brightfield microscopy), activation (Immunocytochemistry), and cytokine production (Luminex assays) were quantified and compared ( N = 4 for each category of sex and race/ethnicity). Results: In a pooled analysis, AF+LPS did not induce glial activation or inflammatory changes compared to AF alone. When stratified by sex, male AF+LPS promoted significant glial activation (high CD11b: p < 0.05; low Iba1: p < 0.01) compared to male AF without LPS; however, this was not associated with changes in pro‐inflammatory cytokines. When stratified by race/ethnicity, AF+LPS induced glial activation in both groups, but a differential increase in pro‐inflammatory cytokines was seen between WH and AA AF (WH‐interleukin‐1β: p < 0.05; AA‐interleukin‐8: p < 0.01). Conclusion: This OOC model of fetal neuroinflammation has determined that race/ethnicity differences do exist for perinatal brain injury. The fetal sex of neonates was not a determining factor of susceptibility to intraamniotic inflammation leading to neuroinflammation.